Effects of Upper-Limit Water Temperatures on the Dispersal of the Asian Clam Corbicula fluminea - Rosa, Inês Correia; Pereira, Joana Luísa; Costa, Raquel; Gonçalves, Fernando; Prezant, Robert (PLOS ONE, 2012)
Temperature is a determinant environmental variable in metabolic rates of organisms ultimately influencing important physiological and behavioural features. Stressful conditions such as increasing temperature, particularly within high ranges occurring in the summer, have been suggested to induce flotation behaviour in Corbicula fluminea which may be important in dispersal of this invasive species. However, there has been no experimental evidence supporting this hypothesis. It was already proven that C. fluminea drift is supported by a mucilaginous drogue line produced by mucocytes present in the ctenidia. Detailed microscopic examination of changes in these cells and quantification of clam flotation following one, two and three weeks of exposure to 22, 25 and 30°C was carried out so that the effects of increasing water temperatures in dispersal patterns could be discussed. Results show that changes in temperature triggered an acceleration of the mucocytes production and stimulated flotation behaviour, especially following one week of exposure. Dilution of these effects occurred following longer exposure periods. It is possible that these bivalves perceive changing temperature as a stress and respond accordingly in the short-term, and then acclimate to the new environmental conditions. The response patterns suggest that increasing water temperatures could stimulate C. fluminea population expansion.
23 citations (Crossref) [2023-10-31]
Keywords: Analysis of variance; Animal behavior; Behavior; Bivalves; Crystallization; Histology; Invasive species; Sediment; dept.aa; peer-reviewed

Handheld app offering visual support to students with autism spectrum disorders (ASDs) - Zamfir, Bogdan; Tedesco, Robert; Reichow, Brian (International Conference on Computers Helping People with Special Needs, 2012)
iPrompts® is a software application for handheld devices that provides visual support to individuals with Autism Spectrum Disorders (ASDs). Caregivers use the application to create and present visual schedules, visual countdown timers, and visual choices, to help individuals with ASDs stay organized, understand upcoming events, and identify preferences. The developer of the application, HandHold Adaptive, LLC, initially introduced iPrompts on the iPhone and iPod Touch in May of 2009. The research team from the Center of Excellence on Autism Spectrum Disorders at Southern Connecticut State University conducted a study of iPrompts in 2010, investigating its use by educators working with students with ASDs. Among other findings, educators indicated a desire to present visual supports on a larger, "tablet"-sized display screen, leading the developer to produce an iPad-specific product, iPrompts® XL. Described in this paper are the research effort of iPrompts and subsequent development effort of iPrompts XL. © 2012 Springer-Verlag.
7 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: ASD; Applications; Autism spectrum disorders; Diseases; Education; Hand held computers; Hand held device; Smartphones; app; application; autism spectrum disorder; dept.aa; handheld device; iPad; iPhone; iPrompts; smartphone; tablet